Soluble urokinase-type plasminogen activator receptor as a measure of treatment response in acute exacerbation of COPD - AboEl-Magd,Gehan Hassan (2018)
ABSTRACT Objective: To evaluate the value of soluble urokinase-type plasminogen activator receptor (suPAR) in the diagnosis of acute exacerbation of COPD (AECOPD) and in monitoring treatment response, analyzing the relationship between suPAR and fibrinogen in AECOPD. AECOPD leads to increased airway inflammation, contributing to an exaggerated release of inflammatory mediators. Methods: We recruited 45 patients with AECOPD and 20 healthy control subjects. Medical histories were taken, and all subjects underwent clinical examination, chest X-ray, pulmonary function tests, and blood gas analysis. On day 1 (treatment initiation for the AECOPD patients) and day 14 (end of treatment), blood samples were collected for the determination of serum suPAR and plasma fibrinogen. Results: Serum levels of suPAR were significantly higher in the AECOPD group than in the control group. In the AECOPD patients, there was a significant post-treatment decrease in the mean serum suPAR level. The sensitivity, specificity, and accuracy of suPAR were 95.6%, 80.0%, and 93.0%, respectively. The Global Initiative for Chronic Obstructive Lung Disease stage (i.e., COPD severity) correlated positively and significantly with serum levels of suPAR and plasma levels of fibrinogen. Conclusions: Monitoring the serum suPAR level can be helpful in the evaluation of the COPD treatment response and might be a valuable biomarker for determining the prognosis of AECOPD. Because serum suPAR correlated with plasma fibrinogen, both markers could be predictive of AECOPD.